Aplikasi Mobile Learning pada Pelajaran Fiqih di MIN 1 Jombang - Zulfah, Machnunah Ani; Afifuddin, Moh; Ashoumi, Hilyah (Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this study, namely 1) to find out how the application of mobile learning learning in fiqh subjects. 2) to find out what factors hinder the application of mobile learning in fiqh subjects, and 3) to determine the supporting factors in the application of mobile learning in fiqh subjects. This research is a qualitative research with descriptive analysis method. Data analysis and research results obtained from observations, interviews, documentation are data reduction, data display, and conclusions / verification.The results of the study show that 1) The application of mobile learning for fiqh subjects initially utilized several supporting applications, which later developed using only watshaap, and e-learning. The use of single sheet lesson plans and various other letter sheets and subjects can be directly accessed on the internet directly without having to go to school. 2) The inhibiting factor of the application of mobile learning is only at the beginning of the transfer of offline files to online. 3) The supporting factors in the application of mobile learning for fiqh learning are, the school facilitates wifi for teachers in schools,and the distribution of free quota assistance to students at MIN 1 Jombang.